The effects of early life polyunsaturated fatty acids and ruminant trans fatty acids on allergic diseases: A systematic review and meta-analysis. Issue 11 (17th June 2019) - Wu, Weijia; Lin, Lizi; Shi, Bijun; Jing, Jin; Cai, Li
ABSTRACT: Early life nutritional exposures could modify the gene expression and susceptibility of allergic diseases (AD). This systematic review aimed to evaluate whether early life (the first 1, 000 days) natural exposure to polyunsaturated fatty acids (PUFA) and ruminant trans fatty acids (R-TFA) could affect the AD risk. We searched PubMed, EMBASE, PsycINFO, Scopus, the Cochrane Library, and ClinicalTrials.gov from inception through September 10, 2017 for relevant full-text articles in English. Observational studies were selected if they examined the effects of early life PUFA or R-TFA on AD (eczema, asthma, wheeze, and allergic rhinitis) or sensitization. The quality of studies was examined by the Newcastle-Ottawa Scale, and the best evidence synthesis (BES) was applied. We included 26 observational studies, and 8 of them showed high quality. BES showed a moderate evidence for the protective effect of vaccenic acid (VA, an R-TFA) on eczema, while insufficient or no evidence was found in other associations. Meta-analysis showed that higher n-6/n-3 ratio and linoleic acid were associated with higher risk of eczema (pooled odds ratio [OR] = 1.06, 95% confidence intervals [CI]: 1.00 −1.13; 1.08, 95% CI: 1.01 −1.15). However, VA was inversely associated with eczema pooled OR = 0.42, 95% CI: 0.25 −0.72). Early life natural exposure to VA showed evident benefit on decreasing the risk of eczema, while PUFA and other R-TFA showed limited effects on AD. More robust studies especially for R-TFA are required.